TABLOIDISASI DALAM PEMBERITAAN TELEVISI (Analisis Isi Terhadap Berita Pemilihan Gubernur DKI Jakarta pada Program Metro Hari Ini dan Kabar Petang Juni-September 2012) - , ADINDA NUSANTARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Local election is one of important process for citizen. Itâs because the election is a place where the citizen can directly show their participation in the political process: electing their own local leader. As media, television plays important role because the citizen still put their belief to get information from it. While the important role of television hasnât fallen down yet, its journalistic quality is decline all the time. Nowadays, âjournalism crisisâ has become a popular term to describe the erosion or decline in the journalism standard. It becomes serious problem because journalism crisis also means a crisis in public communication, because naturally journalism does exist and works to serve the public. This public communication refers to the phenomenon of declining quality (political) journalism as a cause of tabloidization. In this point, all of news standards change. Quality news collapse and is replaced by the news standard which is built to fill other need: entertaining news. With this changing standard, journalistâs orientation is no longer to serve the public by reporting the public interest. But they start looking for trivial reporting which is interest the public, dramatic, low budged, fast, and commercially oriented. At the local election context, this trend of reporting is totally unprofitable for the citizen as a voter, because the need to be well-informed for their decision making. This research aims to study this phenomenon empirically. Using content analysis method, this research finds that tabloidization does exist in the news coverage of DKI Jakarta Local Election 2012, aired by 2 television news channel in Indonesia, Metro Hari Ini (Metro TV) and Kabar Petang (TVOne). The result shows that there is 94% tabloidization component in Metro Hari Ini, also 91,3% in Kabar Petang. Key findings of this study shows the existance of tabloidization component which can be devide in 5 category. First, the use of news topic clearly shows the process of personalization. There is a big gap where the personal issues overlap public issues. Secondly, populist news sources whose role is giving lay knowledge start getting a place. The tendency to supply lay knowledge is supported by the existance of expert actor (news sources) who is set to discuss non-public topic. Third, media also use some sensational effects to give audience more entertaining news. This sensational effects are made in the form of visual manipulation, verbal manipulation (comments), and also audio manipulation (backsound or music). Fourth, there is a decline in factuality level. Accuracy, which is sacred for a news, slowly replaced by speculation, controvercy, and rumors. The last tabloidization that can be viewed is trivialization. This process can be seen through the news atributes. Trivial atributes are the trivial and irrational informations, having no relations deal with DKI Jakarta Local Election.